THE YIELD OF AMARANTH DEPENDING ON THE SOWING METHOD IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE - Tyrus , М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The study examined different methods of sowing Liera amaranth in the Western Forest-Steppe on dark gray podzolized soil. The research years had varying weather conditions compared to the long-term data. In 2020 and 2022, the average temperature during the growing season was 15.3 °C, which was 0.5 °C higher than the long-term data. In 2021, the average temperature was 14.8 °C, corresponding to the long-term average. In terms of precipitation, in 2020, there was 129 mm more than normal, in 2021 – 73 mm more than normal, and in 2022 – 28 mm more than normal. In 2023, there was a decrease in temperature in April and insufficient precipitation in May, with June and July precipitation exceeding the long-term average by 24.4 and 31.7 mm, respectively. The seeds were sown at different row spacings: 15 cm, 30 cm, 45 cm, and 60 cm. The study found that different sowing methods with the same seeding rate resulted in different feeding areas for the plants. For instance, with a 15 cm row spacing, the feeding area was 15×25 cm, and there were 4 plants per 1 meter of row length with a distance of 25 cm between them. With a 30 cm row spacing, the feeding area was 30×14 cm with 7 plants per meter of row length at a distance of 14 cm between them. With a row width of 45 cm, these indicators changed to 45×10 cm and 10 plants and 60×8 cm and 13 plants per meter of row length, respectively. The plant density before harvesting stayed within 22–24 units/m2 and was minimally impacted by the sowing method. Sowing with narrower rows resulted in more even plant placement, and the largest seed mass per plant (17.8 g) was obtained with a 45 cm row spacing. The yield of amaranth grains of the Liera variety was similar at row spacings of 15 cm, 30 cm, and 45 cm, ranging from 3.92–3.97 t/ha. The lowest yield over three years was seen with a 60 cm row spacing, at 3.70 t/ha due to unfavorable conditions created by the elongated rectangle nutrition area (60×8 cm) and dense plant placement. The results were almost the same for other nutrition areas and plant densities.